Peran Hak Tanggungan dalam Pengelolaan Jangka Waktu Hak Guna Bangunan: Suatu Tinjauan Hukum - Mohammad, Prasidya; Lie, Gunardi (UNES Law Review, 2023)
This research explores the role of mortgage rights in the context of managing the duration of building usage rights, with an emphasis on property law aspects. Utilizing a legal review approach, an analysis was conducted on the implications of mortgage rights on the expiration of building usage rights and their impact on property. The study identifies that mortgage rights play a crucial role in influencing the continuity of the duration of building usage rights, while conflicts of interest and the impact of regulatory changes become significant focuses in the dynamics of the relationship between these two rights. The conclusion emphasizes the need for a deep understanding of the role of mortgage rights in the sustainability of building usage rights, the handling of conflicts of interest, and adaptation to regulatory changes in the property law environment.